Transmural Histological Scoring Systems in Crohn's Disease: A Systematic Review With Assessment of Methodological Quality and Operating Properties. (27th January 2020) - Tavares de Sousa, Helena; Estevinho, Maria Manuela; Peyrin-Biroulet, Laurent; Danese, Silvio; Dias, Cláudia Camila; Carneiro, Fátima; Magro, Fernando
Abstract: Background: The relative proportion of inflammation and fibrosis in a stricture is highly relevant in defining the clinical approach for Crohn's disease [CD] patients. Whereas transmural inflammation in CD can be accurately estimated by cross-sectional imaging, evaluating the extent and severity of fibrosis still requires surgical pathology of intestinal resection specimens. This study systematically reviewed all existing transmural histopathological scoring systems developed for the assessment of inflammation and/or fibrosis in CD. Methods: A systematic review of histopathological scoring systems for the assessment of transmural inflammation and/or fibrosis in CD, focusing on originally developed scoring systems. Risk of bias, methodological quality, and operating or psychometric properties [validity, reliability, responsiveness, and feasibility] of each histological scoring system were analysed. Results: A total of 29 original scoring systems were included in this review. Three scoring systems were highlighted as the most widely reproduced, one aimed at assessing inflammation only and two aimed at assessing inflammation and fibrosis. These scores were more widely reproduced probably due to their ease of application in clinical studies. Two highly comprehensive scores were identified, showing good operating properties and high methodological quality, as well as the lowest risk of bias; these should, therefore, be further validated in clinical research studies. Conclusions: This study reviewed all existing transmural histopathological scoring systems for the assessment of inflammation and/or fibrosis in CD and identified the most reliable and accurate scores for clinical research and clinical practice settings.